Stochastic Stability of Processes Determined by Poisson Differential Equations with Delay - Svishchuk, A. V.; Svishchuk, M. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We prove an existence theorem and establish the property of stochastic stability for processes determined by the Poisson stochastic differential equations with delay.